Exploring the Influence of Maternal Health, Education and Socioeconomic Status on Birth Weight in Rural Hospital Settings (IAHS Medical Journal, 2024)
Background: Birth weight is an important indicator of neonatal health and is influenced by various maternal factors. While previous research has explored these factors in different settings, there is limited research focused on rural hospital settings, which face unique challenges. This study aims to investigate the influence of maternal health, education and socioeconomic status on birth weight specifically within rural hospital settings.Materials and methods: The study employed a cross-sectional design and collected data from 138 mothers and their newborn babies in the Upzila Health Complex of Shamnagar, Satkhira between January and May 2023.Results: The results indicated that a significant association exists between birth weight and maternal education levels. Infants born to mothers with higher education levels had a lower likelihood of low birth weight. Similarly, a significant association was found between birth weight and family status, with infants from lower socioeconomic classes having a higher risk of low birth weight. Additionally, the study revealed a significant association between birth weight and maternal nutritional status, with infants of malnourished mothers being at higher risk of low birth weight.Conclusion: This study provides valuable and important insights into the factors influencing newborn birth weight.IAHS Medical Journal Volume 6(1), June 2023; 39-43.